Disability and Gender: The Case of the Philippines - Aubrey D. Tabuga; Christian D. Mina (Philippine Institute for Development Studies (PIDS), 2011)
Addressing gender gaps is a major development objective anywhere in the world. This paper aims to illustrate that this is far more critical in the presence of another social layer â disability. Among persons with disability (PWDs), the gap between men and women are more distinct, their conditions more dismal with poverty as their needs are different. Apart from poverty, discrimination and prejudice are the major challenges that persons with disabilities face in their everyday life. Because they face various social, physical, and economic barriers, policies should gear toward formulating rights-based and comprehensive actions to improve their well-being. In formulation of effective policy actions, data and information are critical. However, data collection on disability in many countries is at an early stage of development because it is given low priority or often excluded from official statistics. The ESCAP noted that the lack of availability and the quality of demographic and socioeconomic indicators concerning disability continue to be major challenges. This paper aims to fill in this information gap. It discusses the conditions of men and women with disability using a set of pioneering surveys conducted in the Philippines. The goal is to illustrate the gender disparities and to draw useful insights on how stakeholders can address this issue.
Keywords: 330; Philippines; persons with disability (PWDs); gender studies; Behinderte; Geschlechterdiskriminierung; Philippinen